Oral Health Awareness Among Pregnant Women: A Cross-Sectional Study - Muhammad Ilyas Baig; Syeda Nadia Firdous; Humaira Naureen; Kishwar Jehandad; Sadaf Shakoor; Nazish Ashfaq, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Health education regarding prevention of oral and dental diseases and their adverse effects during pregnancy may be possible through self-awareness, life style modification and proper hygiene practices. This study aims to find the awareness of oral hygiene and its associated conditions among pregnant women presenting to a tertiary care hospital in Karachi, Pakistan. Methods: This cross sectional study was conducted from June 2023 to July 2024, among pregnant women presented to Alkhidmat hospital Shah faisal Colony Karachi, Pakistan. After getting ethical approval from Baqai dental Hospital (Ref# BDC/ERB/2023/052) and permission from respective hospital administration, pregnant women after their informed consent were interviewed by the principal investigator consecutively. A pre-designed written questionnaire was used. The first section included 6 questions on demographic characteristics of study participants and the second section of the questionnaire included 15 questions of awareness of pregnant women regarding the dental hygiene and conditions associated with it. After data gathering pregnant women were given oral health education and brochure were distributed among them by the principal investigator. The sample size of 281 was estimated by using the Open epi calculator, 24% prevalence of lack of oral health awareness among pregnant women, keeping drop off rate 20% total 392 participants were approached. The data was entered in SPSS version 22.0. The Shapiro-Wilk test was used to check for normality of data. The data was non-parametric therefore Kruskal Wallis test was applied to see the association between demographic variables and oral health awareness among pregnant women. The level of significance was p <0.05. Results: The mean age of study participants was 26.09 ± 5.45 years. Approximately (33.7%) were intermediate/graduates followed by (31.4%) matriculate. Majority of them (84.7%) were housewives and (93.4%) from urban areas. 172(44%) were in their third trimester and 255(65%) were Multipara (2-4 birth). Out of 392 pregnant women more than half 269(68.6%) had inadequate awareness and only 123(31.4%) showed adequate awareness regarding oral health while pregnancy. There was statistically a significant difference between different categories of age, employment status, trimester of pregnancy, parity (p=0.00each) and geographic area (p=0.007) and awareness of oral health among pregnant women. Conclusion: This study concluded that a majority of the pregnant women 269(68.6%) showed inadequate awareness of oral health and its associated conditions during pregnancy. Moreover demographic factors were associated with oral health awareness among them.